2022
DOI: 10.3390/ejihpe12050033
|View full text |Cite
|
Sign up to set email alerts
|

Personal Need for Structure and Fractions in Mathematical Education

Abstract: The research was aimed at finding relations between mathematical knowledge and cognitive individual variable. We realized the experiment with 162 students of the Constantine the Philosopher University in Nitra, Slovakia. We had two variables—the personal need for structure (PNS) as a cognitive-individual variable and knowledge of the fraction as a mathematical variable. The relationships between the factors of the personal need for structure scale and the knowledge of fractions were determined by the IRT model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Our previous studies have shown that math anxiety interferes with cognitive processing. With math anxiety, there is a decrease in working memory capacity, which is also related to students' results in mathematics [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that math anxiety interferes with cognitive processing. With math anxiety, there is a decrease in working memory capacity, which is also related to students' results in mathematics [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is acceptable even for students who are weaker in abstract thinking and mathematical apparatus. As stated in [31], algorithms can be considered structures. As their research shows, the success of the test negatively correlates with the need for structure.…”
Section: Discussionmentioning
confidence: 99%
“…The research undertaken by V. Svecova , L. Rybansky and G. Pavlicova (Constantine the Philosopher University, Slovakia), which is described in [ 4 ], is focused on finding relations between mathematical knowledge and cognitive individual variables. An experiment was realized with 162 students of the Constantine the Philosopher University in Nitra, Slovakia.…”
mentioning
confidence: 99%